INSTITUTIONAL MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDes) ADVANCES TOGETHER IN EMPOWERING THE ECONOMY OF THE PEOPLE OF WANIO VILLAGE, PANCA LAUTANG DISTRICT, SIDRAP REGENCY - Hidayanti, Niniek; Nur, Andi Cudai; Sulmiah, Sulmiah (Universitas Negeri Makassar, 2025)
Thisresearchaimstodeterminethemanagementofvillage-ownedenterprises(BUMDes) moving forward together and empowering theeconomy ofthecommunityinWanioVillage,PancaLautangDistrict,SidrapRegency.Thisresearchisaqualitative descriptive research. Data collection was carried out using observation,interviews and documentation techniques. The results of this researchshow that 1)The achievement of the management of Village-Owned Enterprises (BUMDes) MovingForwardTogetherinEmpoweringtheEconomyoftheWanioVillageCommunity,PancaLautangDistrict,SidrapRegencyhasbeeneffective.2)IntegrationofManagement of Village-Owned Enterprises (BUMDes) Moving Forward Together inEmpowering the Economy of the Wanio Village Community, Panca Lautang District,Sidrap Regency is still not effective, due to the deliberation process being carried out atonlyonepoint.3)AdaptationoftheManagementofVillage-OwnedEnterprises(BUMDes)MovingForwardTogetherinEmpoweringtheEconomyoftheWanioVillageCommunity,PancaLautangDistrict,SidrapRegency.It'sbeengoingwell